2011
DOI: 10.2147/ijn.s23688
|View full text |Cite
|
Sign up to set email alerts
|

PLLA-PEG-TCH-labeled bioactive molecule nanofibers for tissue engineering

Abstract: By mimicking the native extracellular matrix, electrospun nanofibrous scaffolds (ENSs) can provide both chemical and physical cues to modulate cell adherence and differentiation and to promote tissue regeneration while retaining bioresorbable and biocompatible properties. In this study, ENSs were developed to deliver multiple biomolecules by loading them into the core-sheath structure and/or by conjugating them to the nanofiber surfaces. In this work, poly(L-lactide)-poly(ethylene glycol)-NH 2 and poly(L-lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The release profile was continuous thereafter, showing $62% for core-sheath structures for 80 h and $49% for single fibers lasting 10 h. 172 Functionalization of nanofibrous scaffolds with active biomolecules is one of the many strategies adopted in tissue engineering to manipulate and regulate the fate of stem cells within the hierarchical structure within which cells can attach, spread, differentiate, and proliferate. Chen et al 173 functionalized co-spun poly(L-lactide)-polyethylene glycol)-NH 2 and poly(L-lactide) nanofibers with fluorescein isothiocyanate-and rhodamine-labeled bovine serum albumin by activation of amino and carboxyl reactive groups on the surface of nanofibers. In addition, the controlled release of a model drug TCH loaded in the core of the nanofibers was observed.…”
Section: Encapsulation Of Nanoparticles Drugs and Bioactive Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The release profile was continuous thereafter, showing $62% for core-sheath structures for 80 h and $49% for single fibers lasting 10 h. 172 Functionalization of nanofibrous scaffolds with active biomolecules is one of the many strategies adopted in tissue engineering to manipulate and regulate the fate of stem cells within the hierarchical structure within which cells can attach, spread, differentiate, and proliferate. Chen et al 173 functionalized co-spun poly(L-lactide)-polyethylene glycol)-NH 2 and poly(L-lactide) nanofibers with fluorescein isothiocyanate-and rhodamine-labeled bovine serum albumin by activation of amino and carboxyl reactive groups on the surface of nanofibers. In addition, the controlled release of a model drug TCH loaded in the core of the nanofibers was observed.…”
Section: Encapsulation Of Nanoparticles Drugs and Bioactive Moleculesmentioning
confidence: 99%
“…These nanofibers retained their antimicrobial capacity even after their surface functionalization and this indicates that the multi-functional nanofibers could be developed into wound dressings or peritoneal membranes or used in more complicated tissue systems, where multiple growth factors and anti-infection precautions are critical for successful implantation and tissue regeneration. 173 Proteins also have been encapsulated in core-sheath nanofibers and their release studies have been assessed. Zhang et al 174 fabricated fluorescein isothiocyanate-conjugated BSA containing PEG/PCL nanofibers and showed that two different characteristic release profiles could be attained.…”
Section: Encapsulation Of Nanoparticles Drugs and Bioactive Moleculesmentioning
confidence: 99%
“…Co-polymer poly(lactic acid)-poly(ethylene glycol) (PLA-PEG) has been widely used as scaffold materials for tissue engineering due to its excellent biocompatibility and highlighted feasibility of structural modification [18][19][20][21][22][23][24][25][26][27][28]. However, the poor mechanical property and hydrophobicity are main limiting factors for further applications [29,30].…”
Section: Introductionmentioning
confidence: 99%